Effects of Social Power and Distance on the Realization of Requests in Jordanian Bedouin Arabic - Almasaeed, Nedal (Journal of Ethnic and Cultural Studies, 2023)
This study aims to determine the request strategies employed by Jordanian Bedouin Arabic (JBA) native speakers in their interactions in diverse social situations by examining how they realize requests in speech. The study also explores the effect of social power (high, equal, low) and social distance (familiar and unfamiliar) on the realization patterns of requests by highlighting young JBA male speakers’ linguistic choices. Data from 25 young male speakers of JBA were gathered using an Oral Discourse Completion Test (ODCT). The collected data were analyzed based on Brown’s and Levinson’s (1987) politeness theory and following the Cross-Cultural Speech Act Research Project (CCSARP) request strategy coding scheme. The results showed that the participants employed various request strategies according to their occurrences in different contexts. Furthermore, it was found that there is a correlation between perceptions of (im)politeness and social power and distance controlled by the context. The results also showed that the participants employed different sequences of strategies and demonstrated different preferences for context-dependent strategies in their requests.